Core Moderation Values dalam Tradisi Kitab Kuning di Pondok Pesantren - Hisny Fajrussalam (Jurnal al-Thullab, 2020)
In the pesantren tradition, the kitab kuning religious literature is not only a center of study orientation but also a value system that shapes and colors the religious understanding and practices of the pesantren community and surrounding Muslim communities. In the present context, the tradition of pesantren intellectualism can be used as a reference to maintain the values of moderate and tolerant Islamic understanding. The yellow book as the core of the pesantren intellectual tradition is a source of dynamic understanding and pesantren which has proven capable of displaying a friendly face of Islam without anger, as well as being tolerant without hatred. So that Islamic boarding schools as Islamic educational institutions can be the main figures in providing moderate Islamic learning. The study of the yellow book in Islamic boarding schools has contributed greatly to instilling moderate attitudes while realizing Islamic moderation in the boarding school environment. This can be seen from the values of the study of the yellow book used in Islamic boarding schools. Some teaching contexts that lead to the inculcation of moderate attitudes can be found in al-Bājūri's Tījān ad-Darāri book, Al-Jawāhir al-Kalāmiyah fī Iḍāhi al-Aqīdah al-Islāmiyyah by al-Jazairi, Fath al-Qarīb al-Mujīb 'Ala al-Taqrī by Ibn Qāsim al-Gazi and Tafsir Jalālain by al-Mahalli and al-Suyūṭi. AbstrakDalam tradisi pesantren, literatur keagamaan kitab kuning tidak saja menjadi pusat orientasi studi, tetapi juga sistem nilai yang membentuk dan mewarnai paham dan praktik keagamaan komunitas pesantren dan masyarakat muslim sekitarnya. Dalam konteks kekinian, tradisi intelektualisme pesantren dapat dijadikan acuan untuk menjaga nilai-nilai pemahaman keislaman yang moderat dan toleran tersebut. Kitab kuning sebagai inti tradisi intelektulisme pesantren, menjadi sumber pemahaman dinamis dan pesantren yang terbukti mampu menampilkan wajah Islam yang ramah tanpa amarah, serta toleran tanpa kebencian. Sehingga pondok pesantren sebagai lembaga pendidikan Islam dapat menjadi figur utama dalam memberikan pembelajaran Islam yang moderat. Pembelajaran kitab kuning di pondok pesantren telah berkontribusi besar dalam menanamkan sikap moderat sekaligus mewujudkan moderasi Islam di lingkungan pondok pesantren. Hal ini dapat dilihat dari nilai-nilai kajian kitab kuning yang digunakan di pondok pesantren. Beberapa konteks ajaran yang mengarah pada penanaman sikap moderat dapat ditemukan dalam kitab Tījān ad-Darāri karya al-Bājūri, Al-Jawāhir al-Kalāmiyah fī Iḍāhi al-Aqīdah al-Islāmiyyah karya al-Jazairi, Fath al-Qarīb al-Mujīb ’Ala  al-Taqrīb karya Ibn Qāsim al-Gazi dan Tafsir Jalālain karya al-Mahalli dan al-Suyūṭi.